Forced Asset Sales and the Concentration of Outstanding Debt: Evidence from the Mortgage Market - FAVARA, GIOVANNI; GIANNETTI, MARIASSUNTA (Journal of Finance, 2017)
ABSTRACT We provide evidence that lenders differ in their ex post incentives to internalize price‐default externalities associated with the liquidation of collateralized debt. Using the mortgage market as a laboratory, we conjecture that lenders with a large share of outstanding mortgages on their balance sheets internalize the negative spillovers associated with the liquidation of defaulting mortgages and thus are less inclined to foreclose. We provide evidence consistent with our conjecture. Arguably as a consequence, zip codes with a higher concentration of outstanding mortgages experience smaller house prices declines. These results are not driven by unobservable zip code or lender characteristics.